FTIR spectroscopic study of inhibition of chloroxylenol-based disinfectant against salmonella enterica serovar thyphimurium biofilm - Nur Anisah Johari,; Mohd Shafiq Aazmi,; Mohd Fakharul Zaman Raja Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present work was performed to determine the impacts of commercial disinfectants against biomass, viability, and biochemical composition of Salmonella enterica serovar Thyphimurium ATCC14028 biofilm. Salmonella Thyphimurium biofilm grown in microplates was exposed to commercial disinfectants namely sodium hypochlorite, benzalkonium chloride, chloroxylenol, and sodium dodecyl-benzene sulfonate-based disinfectants. Biofilm biomass, biofilm viability, and biochemical composition of the biofilm were determined using crystal violet assay, resazurin assay and Fourier transform infrared (FTIR) spectroscopy respectively. Results demonstrated that, among four commercial disinfectants, chloroxylenol-based disinfectant showed the highest inhibition against S. Thyphimurium biofilm. It remarkably hindered biofilm biomass and biofilm viability at all tested concentrations (0.78%-25%). Half-maximal biofilm inhibitory concentration (BIC50) of chloroxylenol-based disinfectant (5.06%) was found to be the lowest among the tested disinfectants. Meanwhile, S. Thyphimurium biofilm treated with chloroxylenol-based disinfectant exhibited changes in FTIR spectral peaks associated with lipid (1460 cm-1), protein (630 cm-1, 702 cm-1, 1550 cm-1 & 1650 cm-1), and nucleic acid (1080 cm-1 & 1229 cm-1). The findings of the present study suggest that the inhibition of chloroxylenol-based disinfectant against S. Thyphimurium biofilm is mediated by structural changes of biofilm.